2022
DOI: 10.1146/annurev-resource-111820-033252
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformation of the Agricultural Sector In Low- and Middle-Income Economies

Abstract: Movement of labor from agriculture to nonagriculture and the associated increase in farm size through structural transformation are at the core of economic development. We conduct a comprehensive review of the literature exploring the causes and consequences of the transformation. We discuss ( a) the size and determinants for the persisting wage gap between agriculture and nonagriculture, ( b) policy-induced barriers to structural changes, ( c) the role of trade costs and technical change in shaping the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…Earning gaps have been largely attributed to imperfections in land and factors markets that impede the inter-sectoral reallocation of labor (Gollin 2021 ; Deininger et al. 2022 ). Consequently, policies have sought to address factor market imperfections, so that labor could freely move to regulate inter-sectoral labor misallocation and reduce general levels of poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Earning gaps have been largely attributed to imperfections in land and factors markets that impede the inter-sectoral reallocation of labor (Gollin 2021 ; Deininger et al. 2022 ). Consequently, policies have sought to address factor market imperfections, so that labor could freely move to regulate inter-sectoral labor misallocation and reduce general levels of poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Business planning/benchmarking [31,[36][37][38] Knowledge acquisition use of information sources [16,27,29,39,40] Use of business management advice [31,41,42] Machinery sharing [43][44][45][46] Setting goals/targets for business [47,48] Use of integrated pest management (IPM) [20,49] Risk management [41,[50][51][52] Monitoring and evaluation [27,30,40,53] Record keeping [40,48,53] Training for IT skills [16,36] Investment in training programmes (non-IT) [14,25,28,[54][55][56] Changes to standard operating procedures [15,47,56,57] New technology innovations [58][59][60][61] From the perspective of drawbacks, perhaps the most restrictive barrier to a holistic analysis of the rol...…”
Section: Description Of Indicator Literature Source Management Practicesmentioning
confidence: 99%
“…Various studies have identified, at the farm-business level, a number of drivers of productivity change, for example: structural change (e.g., increasing scale) [15], access to education and information [16], cooperation between farmers and with upstream and downstream actors [17], access to new/improved resources [15], climate change [16,18], and technological diffusion and innovation [16,19], among others. While there are a number of these drivers of productivity change, and the importance of these can vary from farm to farm [20], the Organisation for Economic Co-operation and Development (OECD) concludes that the most important driver of productivity improvement is innovation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Development economists began tracing that pattern of structural transformation many decades ago (Chenery, 1960; Clark, 1940; Fisher, 1939; Kuznets, 1957). They note also that agriculture's employment share typically exceeds its GDP share (Deininger et al., 2022; Timmer, 2009). By contrast, the GDP shares of both manufacturing and mining typically exceed their employment shares.…”
Section: Theoretical Literature On Structural Transformation Of a Gro...mentioning
confidence: 99%